Prevalence and predictors of depression and anxiety among oncology patients receiving chemotherapy in public hospitals in Peninsular Malaysia - Remesh Kumar, Mamta Vesudave (2018)
Background: The number of cancer cases in Malaysia has increased from 2008 with 32, 000 cases to 37,000 new cases in 2012. Cancer patients undergoing chemotherapy experienced high level of depression and anxiety. Objectives: To determine the prevalence and predictors of depression and anxiety among oncology patients receiving chemotherapy in public hospitals in Peninsular Malaysia. Methodology: A cross-sectional study was conducted in public hospitals in Peninsular Malaysia. All (N=1356) cancer patients who were Malaysian citizens undergoing chemotherapy were included in this study. The data were collected using self-administered questionnaires. Data were analysed using the Statistical Package for Social Sciences Software (version 22.0). Descriptive statistics was conducted to obtain frequency and percentage of variables. Inferential analysis was done by using chi square or Fisher’s exact test to determine the association between variables at level of significance, p<0.05. Simple logistic regression was used to determine the crude odd ratio and variables with p value <0.25 were entered into the multivariate logistic regression model to determine significant predictors for depression and anxiety. The best predictor was based on adjusted odds ratio. Results: Out of 1356 respondents, all respondents participated in this study. The prevalence of depression was 34.0%. The prevalence of anxiety was 54.8%. The best predictor for depression and anxiety were level of social support. Conclusion: This present study’s finding indicates that the cancer care services should improve in management and intervention on depression and anxiety.